Strategi Guru Dalam Peningkatan Efektivitas Pembelajaran Melalui Penerapan E-Learning Berbasis Web Course Di MI At-Taqwa Bondowoso - Muhammad Ikrom Karyodiputro; Triyana Sapta Ariyani (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to determine the teacher's strategy in increasing the effectiveness of learning through the application of web-based e-learning at Islamic Elementary School At-Taqwa Bondowoso. The research method used is a qualitative method with a type of field research where the research object is Islamic Elementary School At-Taqwa Bondowoso. Data collection techniques using observation, interviews, and documentation. Data analysis was carried out through data reduction activities, data display, as well as drawing conclusions and verification. To test the validity of the data, technical triangulation was carried out. The results showed that the teacher's strategy in increasing learning effectiveness through the implementation of web-based e-learning courses at Islamic Elementary School At-Taqwa Bondowoso, namely through the use of learning media in the form of goggle forms, google classroom, google meet, zoom meet, youtube, and CBT e-learning. The material delivered to students through these media is contextual, adapted to students' needs, situation and class conditions (online), and is directed at how learning can be more meaningful while still emphasizing student involvement in the learning process. Through the implementation of web-based e-learning courses are able to provide a stimulus for teachers and students in an effort to increase digital literacy competence.